WOMEN LEADERSHIP ON PUBLIC INSTITUTION IN MUSLIM MINORITY SOCIETY OF WEST PAPUA - wekke, Ismail Suardi; Ibrahim, Ibrahim (PALASTREN: Jurnal Studi Gender, 2019)
This article focuses on the leadership style, role, and construction of West Papuan women's leadership in politics and education.This research applied case study method.The results show that West Papuan women have several roles in empowering society in different ways.This is indicated by the large number of women in West Papua occupying important positions in the government in West Papua.In addition, education field shows that West Papuan women made many breakthroughs and led several educational institutions in West Papua.In fact, it can be concluded that the role of West Papuan women, both in politics and in education,is not a complement of men, but partners of men in leading and building West Papua.